Analisis Strategi Promosi Menggunakan Company Profile Interaktif dan Media Iklan - Achmad Burhanur Rachman; Marwan Sopi; Widodo Wibisono; Poppy Fitrijanti Soeparan (Universitas Sains dan Teknologi Komputer, 2024)
There are still many institutions and companies that do not have effective and attractive advertising and promotion designs. Efforts are always made so that promotion and advertising have a stronger influence, as well as how to choose efficient media for promotion. Promotion Using Interactive Company Profile and Advertising Media can create added value for an institution and company, either in the form of service excellence or image. The design of this advertising and promotion design is expected to run effectively.